Social Media-Based Marketing Management Strategies to Enhance School Branding at Madrasah Aliyah - Meilina Silvi Imanika (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
This study is to describe and analyze the social media-based marketing management strategies used at MAS YBH Cimindi to improve the school's branding. The background of this study is the importance of a positive image of the school as a private Islamic educational institution in attracting public interest amid increasingly intense competition among educational institutions. The research method used is descriptive qualitative, with data collection techniques including interviews, observations, and documentation. The data analysis technique used the Miles and Huberman method, where data was reduced, presented, and conclusions were drawn. The research results indicate that marketing management strategies are implemented through the stages of planning, organizing, implementing, and evaluating. Additionally, there are three main indicators supporting the enhancement of the school's branding through social media at MAS YBH Cimindi, namely active participation on social media (Instagram, TikTok, and YouTube), creating a positive image through educational and religious digital content, and alumni involvement in school publications and promotions, both conventional and digital. Supporting factors of this strategy include committed human resources of school management, teacher and student participation, utilization of popular platforms, religious academic reputation and alumni involvement. The inhibiting factors are limited competent human resources, lack of promotional budget, competition with other schools, and lack of evaluation and monitoring. The conclusion of this study shows that social media-based marketing strategies are effective in improving the image and attractiveness of MAS YBH Cimindi, but need to be supported by continuous evaluation and innovation.